The Role of the Huamual Police in Handling the Distribution of Liquor in Talaga Negeri Luhu Hamlet, Huamual District, West Seram Regency - Yusuf Safril Wabula; Fatimah Sialana; Louisa M Metekohy (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This research is a qualitative descriptive study that aims to find out how the role of the Huamual Police in Handling the Distribution of Liquor in Talaga Negeri Luhu Hamlet, Huamual District, West Seram Regency. Primary data collection was carried out through interviews with alcohol users who had been involved in brawls and teachers who had a role in preventing brawls between students. Based on the results of the study, it was found that the role of the Huamual Police in Handling the Distribution of Liquor in Talaga Negeri Luhu Hamlet, Huamaul District, West Seram Regency, namely: 1. The actions and steps of the police, especially the Huamual Police in dealing with the distribution of liquor, are quite good because the police referring to and looking at the laws and regulations stated in the legal standards, namely the 1945 Constitution. The obstacles experienced by the police which many experienced in the field included: a.) there was a late report so that the TKP was damaged by people who found witnesses witness in the local community. b) lack of notification or information from the public in seeing the scene of the incident. c.) Witness testimony that was covered up or covered up and not lyrical in giving information to investigators at the TKP.